PENERAPAN MODEL PROBLEM SOLVING TERHADAP KEMAMPUAN LITERASI SAINS SISWA PADA MATERI SISTEM PEREDARAN DARAH DI SMA NEGERI 1 TONDANO - Dewanti P. K Gobel; Ferny M Tumbel; Femmy Kawuwung (LPPM Politeknik Saint Paul Sorong, 2023)
The results of observations made at SMA Negeri 1 Tondano in class XI Science C, students tended to be passive and seemed hesitant to answer questions asked by the teacher. In the learning process, teachers rarely develop students’ literacy skills, because the learning process is more centered on the teacher, which can be seen from the use of less varied learning methods. Limited access to information and lack of interest in reading, on the other hand, lack of understanding of the language used also has an impact on students’ understanding of reading content. The type of research used is Classroom Action Research (PTK) using a problem solver model which aims to improve the literacy skills of class XI IPA C students at SMA Negeri 1 Tondano with a total of 30 students. The data collection process carried out in this research carried out a literacy ability test. The results of the research showed that in cycle I the average value of students’ scientific literacy skills in the content aspect was 67.76% of 30 students, only 18 students met the completeness score with a percentage of 60%, this result is still considered insufficient, after taking corrective action in the cycle II, the results of students’ scientific literacy abilities have increased, namely 80.23% with a percentage of 93%. With this, the application of the problem solving model to the circulatory system material can improve students’ literacy skills.